THE ROLE OF THE RUSSIAN-CHINESE AGREEMENTS IN 1858 AND 1860 IN THE DEVELOPMENT OF RUSSIAN-KOREAN RELATIONS - Karamova, Yuliya; Alikberova, Alfiya (Revista Inclusiones, 2019)
Since the signing of the Russian-Chinese agreements (1858 and 1860), a new stage in the history of Russian-Korean relations begins. With the signing of the Aigun and Beijing treaties, a common border between Russia and the Korean state appears. It is noteworthy that Korea was not aware of the emergence of a common border with Russia. For the first time in the history of the Korean state, a common border appeared with a European state. At that time, the Korean state knew that China had concluded an agreement with France and Great Britain, in which a part of the Chinese territories passed to these states. The emergence of a common border led to the emergence of trade relations. These trade relations gradually expanded, attracting the attention of commercial and industrial circles of Eastern Siberia. The appearance of the common Korean-Russian border led to an active increase in the number of immigrants from the Korean state to the Primorsky Territory. The active resettlement of the inhabitants of Korea and the development of dialogue between Russians and Koreans led to the need to know the language, create dictionaries and study guides for Korean immigrants. The first Russian-Korean dictionary was compiled by M. Putsillo, and the first manual on the Korean grammar where the first explanatory material is given in Russian was developed by priest V. Pyankov.